(untitled) (Conferencea, 2022)
Needs analysis is the primary step of any systematic process. A vast number of scientists pointed out its role in developing materials in teaching and learning contexts. According to Brown (2006), needs analysis is an essential tool that describes learners’ needs to facilitate the curriculum of educational places and has an enormous effect on making the teaching and learning processes more specific. As future EFL/ESL teachers, we have to gain not only teaching skills but also the subtleties of designing courses because language proficiency can be taught only after having a deep comprehension of the learners’ target goals and shortcomings.